HUBUNGAN DUKUNGAN SOSIAL DAN KELUARGA TERHADAP TINGKAT STRES PADA LANSIA - Nanda Farhani Fahmi; Ayu Pratiwi (Nusantara Hasana Berdikari, 2021)
An elderly person who has entered the age of 60 years and over, the elderly are more susceptible to stress. The elderly who experience stress have the potential to experience health problems. Elderly who experienced mild stress (26.86%), moderate stress (17.59%), severe stress (4.16%), very severe stress (5.1%). Elderly people in Indonesia who experience stress usually lack social and family support, therefore the need for social and family support to reduce stress levels in the elderly. Objective: To determine the relationship of social and family support to stress levels in the elderly. Research Method: This study uses literature review. Literary studies can be obtained from various sources from journals, books and articles. By reviewing or reviewing ideas or findings contained in the literature. Research Results: Social and family support in previous studies has a relationship in the influence of stress levels in the elderly. The higher the social and family support given to the elderly the lower the level of stress experienced by the elderly, conversely the lower the social and family support obtained by the elderly the higher the level of stress experienced by the elderly.